Gemoy and Samsul: How The Propaganda Won The 2024 Indonesian Election - Sam, Aisyah; Yusuf, Raidah Intizar; Rahayu, Pramudita Budi (Informasi, 2024)
This study aims to determine the forms of political buzzer propaganda ahead of the 2024 election on Twitter/X. The research method used is a qualitative approach using content analysis and the type of data used is secondary data in the form of tweets or uploads that themed the 2024 presidential election. The data was inputted manually using Microsoft Excel and then analyzed systematically using the SPSS 25 program. The chi square test result is < .001, which means that there are significant differences between candidates in the forms of propaganda. Tweets discussing Prabowo-Gibran were the most propaganda-laden which included name calling, transfer, testimonial, card stacking, and bandwagon, with the exception of plain folks, which is propaganda that shows the efforts of the presidential and vice presidential candidates' closeness to the public, in this category, candidate pair number three, namely Ganjar-Mahfud, is significantly higher than other candidate pairs, and gliterring generalities, namely propaganda with positive connotations on the presidential and vice presidential candidate pairs being discussed, in this case candidate pair number one Anies Imin is significantly higher than other pairs. Name-calling was the most significantly utilized in tweets discussing Prabowo-Gibran, compared to other form of propaganda in tweets discussing the other two candidate pairs. This highlighted the importance of spinning the unfavorable attributes to become a favorable one.